2023
DOI: 10.1021/acs.joc.3c02289
|View full text |Cite
|
Sign up to set email alerts
|

Formation of (Aza)fulvenallene, Cyanocyclopentadiene, and (Aza)fluorenes in the Thermal Rearrangements of Indazoles, Azaindazoles, and Homoquinolinic Anhydride

M. Saeed Mirzaei,
Curt Wentrup

Abstract: Flash vacuum pyrolysis (FVP) of pyrazoles and indazoles constitutes a valuable route to carbenes and nitrenes. In this study, we employed M062X and CCSD(T) calculations to provide a mechanistic rationale for the formation of fulvenallene and fluorenes from indazoles and the corresponding formation of azafulvenallene 15, cyanocyclopentadiene 19, and azafluorenes, e.g. 45, from azaindazoles, e.g. 12, and from homoquinolinic anhydride. The results reveal the importance of initial tautomerization in the pyrazole m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We have investigated the formation and cyclization of nitrile imine 3 at the M06/6-311 + G­(d,p) level of theory (Figure ). The N 2 -elimination from tetrazoles can be described as concerted, one-step reactions. ,, Valence tautomeric diazo compound 2 is found to be an energy minimum in the decomposition of 2-phenyl-5-styryltetrazole 1 , but the concerted N 2 loss (TS3) has a lower overall activation energy (see Scheme and Figures , , and S1 (Supporting Information)). The free energy of activation of 36.4 kcal/mol is in line with the experimental activation energies for several 2,5-disubstituted tetrazoles (34–43 kcal/mol) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have investigated the formation and cyclization of nitrile imine 3 at the M06/6-311 + G­(d,p) level of theory (Figure ). The N 2 -elimination from tetrazoles can be described as concerted, one-step reactions. ,, Valence tautomeric diazo compound 2 is found to be an energy minimum in the decomposition of 2-phenyl-5-styryltetrazole 1 , but the concerted N 2 loss (TS3) has a lower overall activation energy (see Scheme and Figures , , and S1 (Supporting Information)). The free energy of activation of 36.4 kcal/mol is in line with the experimental activation energies for several 2,5-disubstituted tetrazoles (34–43 kcal/mol) .…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, although the energy difference is only 4–5 kcal/mol, Path B is preferred on energetic grounds and, as mentioned above, on mechanistic grounds too. In the analogous rearrangements of 3-phenylindazoles, we also found that the cyclohexadienylidene route (Path B) was preferred …”
Section: Resultsmentioning
confidence: 99%